A Convenient Access to a [2]Rotaxane Proton Shuttle by Using a Fluorous Ponytail - Beyer, Ole; Hesseler, Britta; Lüning, Ulrich (Synthesis, 2015)
The properties of rotaxanes and their constituents, ring and axle, sometimes do not differ much from one another resulting in tedious workup. In the case of a rotaxane designed to shuttle protons across a biological membrane (3–4 nm), molecular weight, shape, and functional groups of axle and rotaxane are similar. But when the macrocyclic ring of the rotaxane carries a fluorous residue, the fluorous effect distinguishes the rotaxane from the axle because the latter carries no fluorine atoms. This concept has been exploited to synthesize a [2]rotaxane in which the macrocyclic ring is protonable and the axle contains a permanent positive charge. Upon protonation/deprotonation of the macrocycle, a shuttling process is induced, which can lead to the transport of protons.
Keywords: rotaxane; trapping; macrocycles; proton transport; fluorine